Агрегат для плющення зерна в потоково-технологічних лініях кормоприготувального відділення молочної ферми - Велит, І. А.; Бондаренко, Д. О.; Велит, И. А.; Бондаренко, Д. А.; Velit, I.; Bondarenko, D. (ЦНТУ, 2018)
У статі представлено аналіз агрегатів для плющення зерна. Розглянуто вибір обладнання в технології процесу приготування кормів. Приведена технологічна схема кормоприготувального відділення молочної ферми. Проаналізовано використання агрегату для плющення зерна в потоково-технологічних лініях концентрованих кормів. Розглянута доцільність використання плющеного зерна в раціоні годівлі на тваринницьких фермах. Проаналізовано вплив способу обробки сухого зерна на надої корів, одержання якісного виробництва молочної продукції. В статье представлен аналіз агрегатов для плющения зерна. Рассмотрены выбор оборудования в технологи процесса приготовления кормов. Приведена технологическая схема кормоприготовительного отделения молочной фермы. Проанализировано использование агрегата для плющения зерна в поточно-технологических линях концентрированных кормов. Рассмотрена целесообразность использования плющенного зерна в рационе кормления на животноводческих фермах. Проанализировано влияние способа обработки сухого зерна на надои коров при получении качественного производства молочной продукции. At this stage of livestock development, the preference is given to the direction associated with the use of special, small-scale, energy-efficient machines and sets of equipment for the mechanization of labor-intensive processes, complete set of flow-technological lines on dairy farms. Choppers of grain components are used to facilitate the preparation of feed for feeding and to improve their animal assimilation on medium-sized dairy farms. In the ration of feeding on dairy farms using rolling the grain. The resulting of crashed of flakes are characterized by the destruction of the internal structure of grains, which facilitates the easier penetration of them and the action of gastric juice in the body of animals. Such a product is characterized by a high degree of digestibility, an increase in the growth of animals on fattening and positively affects the growth of milk yield. The rolling grain is exposed both to wet grain and dry, but the flakes of the wet grain are better absorbed by the animal organism. The purpose of the work is to substantiate the choice of equipment in the technology of the process of preparation of feed in a dairy farm using a unit for rolling the grain, increasing the production of dairy products. The article presents the analysis of aggregates for the rolling of the grain. The choice of equipment in feed preparation technology is considered. The technological scheme of the feed unit of the dairy farm is presented. he use of the aggregate for rolling grain in flow-technological lines of concentrated feed is analyzed.The use of the aggregate for rolling grain in flow-technological lines of concentrated feed is analyzed. The expediency of use of rolling grain in the diet of feeding on livestock farms is considered. The influence of the method of processing dried grains on the livestock of cows, obtaining qualitative production of dairy products is analyzed. Depending on the constructive design, the aggregate for rolling grain has a productivity of 1 to 5 t / h or more, works on all types of grain and legume crops, does not require additional cleaning of grain after the combine, the power of the rolling grain from 1.5 to 12 kW. The grain grinding unit may work like a grinder 3-phase, and single-phase electrical network. Possible drive from the shaft selection power of the tractor's . The aggregate for rolling of the grain saver pays off from one to five months of work, taking into account only the economy of 10% of the grain part of the compound feed with the use of rolling grain compared with the crushed. The use of the aggregate for rolling of the grain in the flow-feed lines positively affects the productivity of animals, the quality of milk, which is especially relevant in modern conditions of farming.
Агрегат для плющения зерна в поточно-технологических линиях кормоприготовительного отделения молочной фермы
Aggregate for Rolling of Grain in Technological Lines of Feed Unit in the Dairy Farm
Keywords: молочна ферма; раціон; потоково-технологічні лінії; агрегат для плющення зерна; молочная ферма; рацион; поточно-технологические линии; агрегат для плющения зерна; dairy farm; ration; flow-technological lines; aggregate for rolling of the grain